Design of microstrip-fed printed UWB diversity antenna with tee crossed shaped structure - Raj Kumar; Gopal Surushe (Engineering Science and Technology, an International Journal, 2016)
A compact, Ultra Wideband (UWB) antenna system for multi-input multi-output (MIMO)/diversity application is proposed. The antenna system is a microstrip structure with two similar triangular shaped radiating elements and a common ground plane. The radiating elements are excited by tapered feed for better impedance matching. A T-crossed shaped stub is added in the ground plane to increase the isolation between the two radiators. The overall dimension of the proposed antenna system is 46 mm × 32.6 mm × 1.6 mm. The measured impedance bandwidth (reflection coefficient < −10 dB) is from 1.8 GHz to well beyond 12 GHz which covers the entire UWB region. A measured isolation of 15 dB or better is achieved in the UWB region. The diversity gain of the antenna system is close to 10 dBi and the envelope correlation coefficient is well below 0.2 in the operating band. Parametric study is also done to check the sensitivity of the antenna in terms of reflection coefficient and isolation to the different parameters. These characteristics show that the proposed antenna is suitable for the MIMO/diversity application.